Association of deep tiny flow voids with prognosis of acute middle cerebral artery atherosclerotic occlusion - Ding, Man-Qiu; Yuan, Wei-Zhuang; Wang, Zi-Jue; Zhang, Yue-Lun; Li, Ming-Li; Xu, Yan; Xu, Wei-Hai (Frontiers in Human Neuroscience, 2025)
BackgroundDeep tiny flow voids (DTFVs) have recently been identified as a novel form of collateral circulation linked to chronic steno-occlusive atherosclerotic middle cerebral artery (MCA) lesions, detectable via high-resolution magnetic resonance imaging (HR-MRI). To date, no study has focused on the presence and clinical significance of DTFVs in acute MCA atherosclerotic occlusion.Materials and methodsThis retrospective study included patients with acute MCA atherosclerotic occlusion from two multicenter HR-MRI cohorts. The incidence of DTFVs and its association with baseline National Institute of Health Stroke Scale (NIHSS) scores, infarct volume, and the proportion of patients with a favorable 90-day clinical outcome defined as a modified Rankin Scale (mRS) ≤ 2 were analyzed.ResultsSixty-six patients (mean age 58.2 ± 9.2 years; 71.2% men) were included. The median time from stroke onset to image was 44.5 (27.3–67.0) hours. DTFVs were identified in 57.6% of patients with MCA atherosclerotic occlusion. After adjusting the potential confounders, DTFVs were significantly associated with lower baseline NIHSS scores (β, −3.68; 95% CI, −6.30, –1.07; p = 0.007), smaller infarct volume (β, −40.88; 95% CI, −70.15, −11.60; p = 0.007), and a higher proportion of patients with favorable 90-day clinical outcome (OR, 6.03; 95% CI, 1.39–26.19; p = 0.017).ConclusionThe presence of DTFVs was correlated with a favorable outcome in patients with acute MCA atherosclerotic occlusion. Improved recognition and awareness of this imaging marker of collaterals could help understand the varying infarct evolution seen in MCA occlusion and contribute to more individualized management and treatment.